Developed molecular dynamics method of dissipative particle dynamics for the bench mark numerical simulation of fluid flow inside a rectangular chamber - Yaghoubi, Somaye; Rezaye, Behzad; Sajadi, S. Mohammad; Shahgholi, Mohamad; İnç, Mustafa (Elsevier Sci Ltd, 2023)
The fluid flow inside the chamber with a moving wall is simulated by developed Dissipative Particle Dynamics (DPD) method which implies the developed molecular dynamics (MD) appraoch. In this benchmark problem, the chamber is filled with a fluid with a certain initial temperature and its cover is moving at a constant speed. One of the most important issues in DPD method, is creating solid walls and then applying related boundary conditions. Hence by freezing several layers of DPD particles, solid walls were created to prevent DPD particles from leaving the area. Then, by applying the boundary condition of parallel reflection, the penetration of fluid particles into the solid wall was prevented, and the no-slip condition was applied to the walls. Next, the effect of parameters such as initial distribution of fluid particles, their initial velocity, geometry of the problem, boundary conditions, Reynolds number and different weighting functions, were investigated. It was showed that increasing Reynolds number to more than 800 in addition to eliminating the incompressibility property caused particles exit from the solution domain and diverge. It is also possible to increase the Schmidt number of DPD fluid by applying a suitable weighting function.
Keywords: Dynamics of wear particle; Collimated reflection; DPD; MD; Incompressibility